Inferiority and Compensation in the Main Character of Intan Paramaditha’s Short Story Perempuan Buta Tanpa Ibu Jari - Tifani Safira Mayasari; Ririe Rengganis (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research is driven by the importance of understanding the representation of women's psychological experiences in contemporary Indonesian literature, which frequently portrays practices of social marginalization. A significant work in this field is the short story “Perempuan Buta Tanpa Ibu Jari" by Intan Paramaditha, which depicts main characters facing profound internal conflicts and marginalization within a patriarchal system. This study aims to examine the forms of inferiority and psychological compensation strategies used by main characters through the lens of Alfred Adler’s individual psychology. The methodology employed is qualitative descriptive with a literary psychology approach. The analysis demonstrates that the characters' inferiority is rooted in domestic marginalization and social stigma, which is subsequently compensated for through extreme body control, manipulative material strategies, and the use of horror narratives as a mode of symbolic resistance. Consequently, the horror elements in the story serve as a representation of the psychological processes used to confront social pressures and achieve a fictional final goal.